Comparison of readiness for e-learning from the perspective of students and professors of Medical Sciences - Parisa Mokaripour; Nasrin Shokrpour; Leila Bazrafkan (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: The aim of this study was to evaluate the cognitive, psychomotor, and attitudinal readiness of faculty members and students of Shiraz University of Medical Sciences for using e-learning in 2019 in order to move toward the desired future of e-learning in medical education, promote the benefits of e-learning in the country, and provide training to each of the research groups if needed. METHODS: This is a cross-sectional study conducted in Shiraz University of Medical Sciences, Iran, in 2019. The study population consisted of 379 students and 281 professors selected through the systematic random sampling in Shiraz University of Medical Sciences. The e-learning readiness questionnaire developed by Zarif Sanaei et al. was used to evaluate the students' and teachers' viewpoints. RESULTS: The results showed that the average level of skill, knowledge, and attitude among students and teachers was positive and higher than the mean (P < 0.05). It had only a significant relationship in the level of education of the teachers and the marital status of the participants. There was also a significant interaction between skill, knowledge, and attitude. CONCLUSION: There is a need for successful implementation of e-learning by creating appropriate infrastructure, applying the required standards, as well as taking measures to reduce the existing resistance in this regard, which can be achieved through training workshops. The experience of successful universities in the country and abroad can also be used to implement e-learning.